A prospective, randomized, single-center, two-arm, open-label study to evaluate the efficacy of biotherapi®, a two-strain bacillus probiotic blend, as an adjunctive therapy in the treatment of rheumatoid arthritis - Arindam Nandy Roy; Yarram Ashok Kumar; Syeda Sana Fatima (Indian Journal of Rheumatology)
Objective: Probiotics have been shown to alleviate the symptoms of rheumatoid arthritis (RA) by normalizing the composition of gut microbiota. The objective of this study was to evaluate the effect of twice-daily Biotherapi® (Sanzyme Private Limited, India) as an adjunct to standard of care on disease activity and functional ability of patients with RA. Methods: In this prospective, randomized, single-center, two-arm, open-label study, patients were randomized (1:1) to receive twice-daily adjunctive Biotherapi® (n = 125) or standard of care alone (n = 125) for 12 weeks. The primary endpoint was the change from baseline to days 45 and 90 in the Disease Activity Score-28-erythrocyte sedimentation rate (DAS-28-ESR). Results: Standard of care alone and adjunctive Biotherapi® significantly reduced the mean DAS-28-ESR at days 45 and 90 (P < 0.05). However, the reduction from baseline was greater in patients receiving adjunctive Biotherapi® compared to standard of care alone at day 45 (–0.67 ± 0.77 vs. −0.15 ± 0.84, P < 0.0001) and day 90 (–1.21 ± 0.99 vs. –0.48 ± 0.69, P < 0.0001). Consequently, compared to standard of care, more patients achieved remission (4.3% vs. 23.6%) and showed good (6.52% vs. 35.45%) and moderate (31.5% vs. 41.81%) European League Against Rheumatism response at 90-day Biotherapi®. A similar pattern of improvement in the scores including Health Assessment Questionnaire was observed. No clinically significant changes in the laboratory parameters were reported during the study. Conclusion: Twice-daily supplementation with Biotherapi® probiotic blend as an adjunct to standard-of-care treatment for RA is beneficial for alleviation of severity and symptoms of the disease and results in improvement in patients' quality of life.